Sizing and Cost Analysis of Self-Consumed Solar PV DC System Compared with AC System for Residential House - T. M. N. T. Mansur; N. H. Baharudin; R. Ali (Institute of Advanced Engineering and Science, 2018)
The use of solar photovoltaic (PV) system has grown significantly in Malaysia after Renewable Energy Act has been gazetted in 2011.The objective of this paper is to highlight the technical and economic analysis of solar PV DC system to generate enough energy for residential customer group that consumed 200 kWh per month so that they are less dependent on energy from the utility grid. The results are then compared to the solar PV AC system with similar load setup. The methodology involves gathering solar energy resource, configuring daily load demand, sizing PV array, battery bank and inverter and lastly simulation of the design system by using Homer software. Based on Homer simulation, the solar PV AC system required slightly larger PV array sizes than the solar PV DC system to compensate losses due to the inverter efficiency which is not counted in DC system.Moreover, the solar PV AC system is almost 8.0% more expensive with 6% higher COE than the solar PV DC system due to the present of inverter.Lastly, both systems will benefit from reduction of energy consumed up to 2,434 kWh annually and to the environmental aspect, will avoid 1.7 tons of CO2 releases into the atmosphere.